Genomic Surveillance Enables the Identification of Co-infections With Multiple SARS-CoV-2 Lineages in Equatorial Guinea - Hosch, Salome; Mpina, Maxmillian; Nyakurungu, Elizabeth; Borico, Nelson Silochi; Obama, Teodora Mikumu Alogo; Ovona, Maria Carmen; Wagner, Philipp; Rubin, Sarah E.; Vickos, Ulrich; Milang, Diosdado Vicente Nsue; Ayekaba, Mitoha Ondo'o; Phiri, Wonder P.; et al. (Frontiers in Public Health, 2022)
COVID-19 disease caused by SARS-CoV-2 represents an ongoing global public health emergency. Rapid identification of emergence, evolution and spread of SARS-CoV-2 variants of concern would enable timely and tailored responses by public health decision-making bodies. Yet, global disparities in current SARS-CoV-2 genomic surveillance activities reveal serious geographical gaps. Here, we discuss the experiences and lessons learned from the SARS-CoV-2 monitoring and surveillance program at the Public Health Laboratory on Bioko Island, Equatorial Guinea that was implemented as part of the national COVID-19 response and monitoring activities. We report how three distinct SARS-CoV-2 variants have dominated the epidemiological situation in Equatorial Guinea since March 2020. In addition, a case of co-infection of two SARS-CoV-2 variants of concern, Beta and Delta, in a clinically asymptomatic and fully COVID-19 vaccinated man living in Equatorial Guinea is presented. To our knowledge, this is the first report of a person co-infected with Beta and Delta variants of concern globally. Rapid identification of co-infections is relevant since these might provide an opportunity for genetic recombination resulting in emergence of novel SARS-CoV-2 lineages with enhanced transmission or immune evasion potential.